Dewey's theory of moral values - Cornelius, Benjamin Ebenezer (The University of Edinburgh, 1924)
Our aim in this thesis will he critically to study Dewey’s theory of moral values witn a view to discovering hew far the naturalistic, biological point of view, as this is conceived by Dewey, is capable, when applied in the realm of Ethics, of adequately interpreting the facts of moral life. For this purpose, we snail begin with a critical study of Dewey's biological psychology, which we shall find in the end to be responsible for his entire ethical theory, followed by a critical study of his nominalistic Logic, which, in our opinion, is the result of ^ psychology and comes to determine his views A in Ethics. These two sections, then, since they provide a criticism of the basic ideas on which Dewey’s ethical theory is built, will be dealt with at some length. The third and fourth sections will be concerned with a statement and criticism of Dewey’s ethical theory.
A critical study of Dewey's theory of moral values